KOMPARASI PRODUKTIVITAS DAN AKURASI PESAWAT UDARA NIRAWAK UNTUK SURVEI FOTOGRAMETRI PADA PROYEK JALAN - Amirrudin Ahmad, Ali; Lyhardo Sidabutar, Yosevel; Shelvira Herwieany, Agnes (Jurnal Jalan Jembatan, 2024)
Unmanned Aerial Vehicles (UAVs), commonly known as drones, are aerial devices equipped with cameras and sensors for various applications, including aerial mapping surveys. The growth of UAV technology has provided significant benefits in the construction industry by enabling accurate and efficient spatial data collection for 3D modelling, progress monitoring and work volume analysis. Various characteristics of UAVs, including wing type, size, coverage and capabilities, accompany the development of UAVs. The diversity of types and brands of UAVs on the market is a challenge for organizations in determining the choice of UAVs that suit their needs and intended use. This research aims to provide recommendations for UAVs in mapping survey activities by comparing productivity and accuracy. In this research, we compare 3 (three) different types of UAV, namely DJI Phantom 4 Pro V2, DJI Mavic 3 Enterprise RTK, and WingtraOne Gen II, combined with two types of geotagging methods, namely GCP (Ground Control Point) and PPK (Post Processing Kinematic). Research carried out on 31 January 2023 at the Cimanggis-Cibitung Toll Road Project Section 2 location obtained the best accuracy results of 0.08 m horizontally and 0.07 m vertically from the WingtraOne Gen II PPK method, while DJI Mavic 3 RTK Enterprises obtained the best productivity comparison results with productivity of 2.90 ha/min. In general, for using photogrammetric survey technology on long continuous road projects, it is recommended to use portable UAVs and the capabilities of the PPK and RTK methods, with the primary consideration being accuracy and productivity. The research results can provide insight into the optimal combination of PUNA and geotagging methods in using photogrammetry in the construction industry. Keywords: UAV, photogrammetry, geotagging, construction project, toll road